Current trends and challenges in the synthesis and applications of chitosan-based nanocomposites for plants: A review. (1st June 2021) - Yu, Juntong; Wang, Depeng; Geetha, Nagaraja; Khawar, Khalid Mahmood; Jogaiah, Sudisha; Mujtaba, Muhammad
Graphical abstract: Highlights: Chitosan is an eco-friendly and multipurpose polymer that can be utilized in plant production. Chitosan can be composited with many other elements and polymers. Chitosan-based nanocomposites have a wide potential in plants. Delivery of nutrients, pesticides, biomolecules such as DNA, siRNA, CRISPR is possible via chitosan. Optimization of protocols for large-scale production of chitosan products is the need of the day. Abstract: Chitosan, a low-cost and multipurpose polymer with numerous desired physicochemical and biological properties has been tested for various applications in agriculture, pharmacy, and biomedicine industries. The availability of functional groups along the backbone makes chitosan readily available for other polymers and metal ions to form bio-nanocomposites. Different types of chitosan-based nanocomposites have been designed and tested for the enhancement of chitosan efficiency and ultimately widening the application areas of chitosan in plants. These nanocomposites serve different purposes such as eliciting plant's defence systems against different threats (pathogen attack), antimicrobial agent against bacteria, fungi and viruses, enhancement of nutrient uptake by plants, control release of micro/macronutrients, fungicides and herbicides. In this review, an extensive outlook has been provided (mainly in the last five years) to recent trends and advances in the fabrication and application of chitosan-based composites. Finally, current challenges and future development opportunities of chitosan-based nanocomposites for plants are discussed.